An Update on African Trypanocide Pharmaceutics and Resistance - Kasozi, Keneth Iceland; MacLeod, Ewan Thomas; Ntulume, Ibrahim; Welburn, Susan Christina (Frontiers in Veterinary Science, 2022)
African trypanosomiasis is associated with Trypanosoma evansi, T. vivax, T. congolense, and T. brucei pathogens in African animal trypanosomiasis. Suramin sodium suppresses ATP generation during the glycolytic pathway and is ineffective against T. vivax and T. congolense infections. Resistance to suramin is associated with pathogen altered transport proteins. Melarsoprol binds irreversibly with pyruvate kinase protein sulfhydryl groups and neutralizes enzymes which interrupts the trypanosome ATP generation. Melarsoprol resistance is associated with the adenine-adenosine transporter, P2, due to point mutations within this transporter. Eflornithine is used in combination with nifurtimox. Resistance to eflornithine is caused by the deletion or mutation of TbAAT6 gene which encodes for the transmembrane amino acid transporter that delivers eflornithine into the cell, thus loss of transporter protein results into eflornithine resistance. Nifurtimox alone is regarded as a poor trypanocide however it is effective in melarsoprol-resistant gHAT patients. Resistance is associated with loss of a single copy of the genes encoding for nitroreductases enzymes. Fexinidazole is recommended for first-stage and non-severe second-stage illnesses in gHAT and resistance is associated with trypanosome bacterial nitroreductases which reduce fexinidazole. In AAT, quinapyramine sulphate interferences with DNA synthesis and suppression of cytoplasmic ribosomal activity in the mitochondria. Quinapyramine sulphate resistance is due to variations in the potential of the parasite’s mitochondrial membrane. Pentamidines create cross-links between two adenines at 4 to 5 pairs apart in adenine-thymine-rich portions of Trypanosoma DNA. It also suppresses type II topoisomerase in the mitochondria of Trypanosoma parasites. Pentamidine resistance is due to loss of mitochondria transport proteins P2 and HAPT1. Diamidine most effective against Trypanosome brucei group and acts via the P2/TbAT1 transporters. Diminazene aceturate resistance is due to mutations that alter the activity of P2, TeDR40 (T. b. evansi). Isometamidium chloride is primarily employed in the early stages of trypanosomiasis and resistance is associated with diminazene resistance. Phenanthridine (Homidium bromide, also known as ethidium bromide) acts by a breakdown of the kinetoplast network. Homidium resistance is comparable to isometamidium. In humans, the development of resistance and adverse side effects against monotherapies has led to the adoption of Nifurtimox-eflornithine combination therapy.